Small‐vessel PCI outcomes in men, women, and minorities following platinum chromium everolimus‐eluting stents: Insights from the pooled PLATINUM Diversity and PROMUS Element Plus Post‐Approval studies. Issue 1 (21st January 2019) - Guedeney, Paul; Claessen, Bimmer E.; Mehran, Roxana; Kandzari, David E.; Aquino, Melissa; Davis, Scott; Tamis, Luis; Wang, John C.; Othman, Islam; Gigliotti, Osvaldo S.; Haghighat, Amir; Singh, Sarabjeet; et al.
Abstract: Objective: We evaluated 1‐year outcomes after platinum chromium everolimus‐eluting stents (PtCr‐EES) in small versus non‐small coronary arteries within a large, diverse sample of men, women, and minorities. Background: There exists limited outcomes data on the use of second‐generation drug‐eluting stent to treat small diameter coronary arteries. Methods: We pooled patients from the PLATINUM Diversity and PROMUS Element Plus stent registries. Small‐vessel percutaneous coronary intervention (SV‐PCI) was defined as ≥1 target lesion with reference vessel diameter (RVD) ≤2.5 mm. Endpoints included major adverse cardiac event (MACE; death, myocardial infarction [MI] or target vessel revascularization [TVR]), target vessel failure (TVF; death related to the target vessel, target vessel MI or TVR) and definite/probable stent thrombosis (ST). Multivariable Cox regression was used to risk‐adjust outcomes. Results: We included 4, 155/4, 182 (99%) patients with available RVD, of which 1, 607 (39%) underwent small‐vessel PCI. SV‐PCI was not associated with increased MACE (adjHR 1.02; 95%CI 0.81–1.30) or TVF (adjHR 1.07; 95%CI 0.82–1.39). MI risk was lower in white men compared to women and minorities, both in the setting of SV‐PCI (adjHR 0.41; 95%CI 0.23–0.74 and adjHR 0.39; 95%CI 0.20–0.75, respectively) and for non‐SV‐PCI (adjHR 0.61; 95%CI 0.38–0.99 and adjHR 0.45; 95%CI 0.27–0.74, respectively). There was no significant interaction between RVD and sex or minority status for any endpoint. Conclusion: In a large diverse contemporary PCI outcomes database, SV‐PCI with PtCr‐EES was not associated with increased MACE or TVR and did not account for the increased MI risk noted in women and minorities compared to white men.